Penggunaan Model Pembelajaran Kooperatif Tipe Team Game Tournament (TGT) Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran PAI - Khusna, Diana Ni'matul; Nursafitri, Laila; Sari, Nur Indah (Universitas Muhammadiyah Tangerang, 2024)
Student learning outcomes are determined by the teacher's strategic role in teaching and learning activities. Learning will feel boring for students if it only focuses on the teacher, while the students' activities are just listening. It is important for teachers to choose a learning model that involves students during the learning process. One of them is the Team Game Tournament (TGT) type cooperative learning model. This research aims to improve student learning outcomes in Islamic Religious Education subjects in class VII Rangkayo Rasuna Said SMP IT Baitul Muslim by using the Team Game Tournament (TGT) type cooperative learning model. This type of research is Classroom Action Research (CAR) with two cycles consisting of four stages, namely planning, implementation, observation and reflection. Class VII student Rangkayo Rasuna Said SMP IT Baitul Muslim is the research subject. The data collection methods are observation and tests. Data were analyzed using qualitative and quantitative data analysis. The research results are: 1) student learning outcomes during the pre-cycle were 56% of students completed, meaning student learning outcomes in PAI subjects were still low. 2) the use of the TGT type cooperative learning model can increase student learning outcomes in PAI subjects, namely in cycle I by 67% to 87% in cycle II. 3) student learning activity increased from 69% in cycle I to 87% in cycle II. Based on these results, this research achieved classical completeness.